(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A coalition government is a form of government in which political parties cooperate with each other for formation of a government. Reason for such an arrangement is that no single party has achieved an absolute majority after an election. This paper has highlighted on coalition government in India.